Personality traits - Matthews, Gerald (Cambridge University Press, 2009)
Now in its third edition, this dynamic textbook analyses the traits fundamental to human personality: what they are, why they matter, their biological and social foundations, how they play out in human life and their consequences for cognition, stress and physical and mental health. The text also considers the applications of personality assessment in clinical, educational and occupational settings, providing the reader with a detailed understanding of the whole field of personality traits. This edition, now with improved student features, includes the latest research from behavioural genetics, neuroscience, social psychology and cognitive science, assesses the impact of new research techniques like brain imagery, and provides additional content on positive aspects of traits and practical uses of personality assessment. This is an essential textbook for students taking courses in personality and individual differences and also provides researchers and practitioners with a coherent, up-to-date survey of this significant area.